READING OF DA'WAH AND RELIGIOUS MODERATION THROUGH MAQĀṢID AL-SYARĪ'AH IN INDONESIA - Yuli Andriani; Mohd. Khairul; Armadila; Neng Ayu Saadah; Dafrizal (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2025)
The fragmentation of da'wah in the digital space shows that normative and moralistic approaches alone are not enough to explain the complexity of the issue of religious moderation, especially when da'wah is confronted with radicalism, hate speech, and religious disinformation. Through a qualitative approach, Maqāṣid al-syarī'ah as a framework of analysis in rereading da'wah today. The findings of the study are maqāṣid al-syarī'ah being a theoretical perspective that explains the relationship between da'wah, religious moderation, and social challenges. Da'wah is a social practice that is directed at the goals of sharia in building a moderate, inclusive, and civilized religious life in the midst of Indonesia's pluralistic society.